Information society with Chinese characteristics - Hong, Yu (Javnost (Ljubljana), 2008)
By focusing on the Chinese official discourse of "neoindustrialisation" published on the People's Daily, this article not only provides an understanding of the Chinese official understanding of information society and information economy, but also foregrounds the issue of information in China's conflicted reintegration with global capitalism. This article argues that, deviant from the Western discourse of post-industrialism, the neo-industrialisation strategy promotes a coordinated effort to both "industrialise" and "informationise" the economy. Moreover, pragmatic concerns with China's realities, including unfinished industrialisation, structural unemployment and the domestic demands for all-around national development, all find echoes in the discourse of neo-industrialisation. By providing a politicaleconomic contextualisation of this discourse, this article also strives to provide an insight of the most recent plan of forming a "super" Ministry of Industry and Information Technology in the Chinese government, which was announced in March 2008.
Keywords: Kitajska; tržno gospodarstvo; kapitalizem; capitalism; industrializacija; postindustrijska družba; informacijska družba